Sustainability status of ecotourism-based seagrass ecosystem management on Maitara Island. Indonesia - Salim Abubakar; Rina Rina; Riyadi Subur; Rene C Kepel; Sunarti Sunarti; Rugaya H Serosero; Yuyun Abubakar; Nebuchadnezzar Akbar; Najamuddin Najamuddin; M. Janib Achmad; Ariyati H. Fadel; M. Said Al Hadad; Raut Nugrahening Widhi; Raut Wahyuning Paluphi (Depik, 2025)
Seagrass ecotourism is a tourism activity based on seagrass ecosystem as an educational tour by seeing the ecology of seagrass meadows and associated biota. Conservation awareness and improving community welfare, seagrass ecotourism is a nature-based tourism strategy with the aim of environmental conservation and containing aspects of community education and culture. Determining the sustainability status of seagrass ecosystem management is very important as a basis for future policy planning. The sustainability of seagrass ecosystems needs to be protected, so a policy strategy is applied in sustainable seagrass ecosystem management. The objectives of the study are: 1) determining the sustainability status of ecotourism-based seagrass ecosystem management based on ecological, economic and social dimensions, 2) determining the policy strategy for ecotourism-based seagrass ecosystem management. The results of the study obtained the sustainability status of ecotourism-based seagrass ecosystem management based on ecological dimensions is quite sustainable while the economic and social dimensions are less sustainable. The strategy for sustainable policy for managing seagrass ecosystems based on ecotourism on Maitara Island, Tidore Islands, namely education about seagrass ecosystems for the community, managing seagrass ecosystems based on ecotourism, increasing seagrass rehabilitation programs, maximum limits for carrying capacity of seagrass ecotourism, training for developing managers of seagrass ecotourism based on ecosystems, increasing job opportunities and business opportunities, legality of seagrass areas as conservation areas in the tourism utilization zone category and strengthening laws and institutions.Keywords:analysismultidimensionalsmall islandsustainabilitytourism